A review of the genus Eugoa Walker (Lepidoptera, Erebidae, Arctiinae, Lithosiini) in Cambodia, with the description of a new species - Bayarsaikhan, Ulziijargal; Bucsek, Karol; Bae, Yang-Seop (Zootaxa, 2018)
Eugoa Walker (Arctiinae, Lithosiini) from Cambodia is reviewed. The genus counts with 20 species in this country, including Eugoa arguta Bayarsaikhan & Bae, n. sp., and three newly recorded species, E. vasta van Eecke, 1920, rest. comb., E. formosicola (Matsumura, 1927), n. st. and E. kuznetzovi Dubatolov & Bucsek, 2016. Besides our revalidation of Eugoa bipunctata formosicola as a valid species, it was also discovered to have a synonym: E. cesaneki Bucsek, 2008 n. syn. Moreover, females of E. lucea Bucsek, 2012, E. nata Dubatolov & Bucsek, 2013, and E. kuznetzovi Dubatolov & Bucsek, 2016 are described and illustrated for the first time. A key to the Cambodian species of the genus Eugoa with illustration of adults and genitalia are provided.